The Extent, Nature and Potential Impact of Food Company Sponsorship of Children’s Sports in Two Policy Environments in Canada - Pauzé, Elise (Université d'Ottawa | University of Ottawa, 2026)
Exposure to unhealthy food marketing is a known determinant of children’s poor dietary behaviours. This research sought to 1) assess the extent and nature of children’s exposure to food marketing stemming from the sponsorship of their sporting activities and 2) examine the benefits that sports clubs derive from this sponsorship in Canada’s two policy environments, namely Quebec, where commercial advertising directed to children under 13 years is restricted, and other provinces, where food advertising is self-regulated by the food industry. Broadly, two online surveys found that a large share of children (40-67%) aged 10-17 years who played on a sport team recalled being exposed to food advertising in amateur sports settings. In both surveys, children in Quebec were less likely to report exposure to food advertising on their sports equipment than children living in other provinces. However, differences among children aged 10-12 years protected by Quebec’s advertising restrictions compared to older children in the province were not statistically significant. Differences in reported exposure to most other types of food advertising (e.g. branded sports awards, free food, coupons) among children living in Quebec compared to those in other provinces and among Quebecois children protected versus not protected by provincial restrictions were also not found to be statistically significant. Correspondingly, a telephone survey with a small sample of children’s sports clubs found that at least 45% of those surveyed in Ontario (21/47) and 55% in Quebec (22/40) were sponsored by a food company, most frequently fast-food restaurants. Sports clubs received funding and in-kind benefits such as free food, uniforms and medals. For most clubs, this funding and the perceived value of in-kind benefits was small relative to the club’s total revenue. In both provinces, food company sponsors, particularly fast-food restaurants, were reported as being promoted on uniforms, sports equipment, and sports awards, more often on those for children aged 12 years and under. Overall, these findings suggest amateur sports settings constitute an important source of exposure to food marketing among children. Quebec’s advertising restrictions are not adequately limiting children’s exposure to sponsorship-related food marketing, including prominent forms (e.g. branded uniforms) that reach children under 13 years. The food industry’s self-regulatory code also does not limit many forms of sponsorship-related marketing that were reported. Policymakers should consider adopting statutory restrictions on the sponsorship of children’s sports by food companies associated with unhealthy products.
Keywords: Food marketing; Sports sponsorship; Consumer Protection Act; Industry self-regulation; Brand marketing